2019
DOI: 10.1149/2.0701914jes
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking How External Pressure Can Suppress Dendrites in Lithium Metal Batteries

Abstract: Lithium metal anodes are critical enablers for high energy density next generation batteries, but they suffer from poor morphology control and parasitic reactions. Recent experiments have shown that an external packing force on Li metal batteries with liquid electrolytes extends their lifetimes by inhibiting the growth of dendritic structures during Li deposition. However, the mechanisms by which pressure affects dendrite formation and growth have not been fully elucidated. For

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
115
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 134 publications
(117 citation statements)
references
References 95 publications
1
115
1
Order By: Relevance
“…Yurkiv et al 88,89 studied the influence of the stress and the SEI on Li electrodeposition, and reproduced filament structure of Li observed in experiments. Harris et al 90 studied the effect of external pressure on the dendrite growth in lithium metal batteries. Their results showed that if there is sufficient local stress, Li avoids plating at the tips of growing Li dendrite.…”
Section: Stress Evolution and Fracturementioning
confidence: 99%
“…Yurkiv et al 88,89 studied the influence of the stress and the SEI on Li electrodeposition, and reproduced filament structure of Li observed in experiments. Harris et al 90 studied the effect of external pressure on the dendrite growth in lithium metal batteries. Their results showed that if there is sufficient local stress, Li avoids plating at the tips of growing Li dendrite.…”
Section: Stress Evolution and Fracturementioning
confidence: 99%
“…Second, it is important to note that Li tends to grow in denser morphology when electrodeposited under pressure, as is also shown in Harrison et al (2017). This denser morphology may be related to a mechanical overpotential associated with pressure at the interface, which provides an energy barrier preventing growth in the direction of the applied compression; instead, this overpotential provides an incentive for Li to grow in the lateral direction perpendicular to the applied compression and may lead to much denser films (Zhang et al, 2019). In the films electrodeposited at 1000 kPa, we hypothesize that the dense Li crystallites and the incentive to grow laterally may cause neighboring crystallites to compress one another and locally confine the film so as to enable a compressive in-plane strain.…”
Section: Origin Of Compressive Strain In LI Filmsmentioning
confidence: 99%
“…A further drop in overpotential is seen when the c-LPS at 100 o C under 1.5 MPa external pressure is subjected to an increase in pressure to 7 MPa. High pressure increases the interfacial contact and can decrease the surface roughness of the Li metal as well, improving the performance 52,63 . We For high current operations, we need to operate the cell under high external pressure > 10 MPa which smoothens out the interfacial perturbations to less than 100 nm utilizing a low shear modulus /1 SE Li GG  .…”
Section: Experimental Validationmentioning
confidence: 99%